2017
DOI: 10.1590/1679-395158473
|View full text |Cite
|
Sign up to set email alerts
|

Partnership inside Governance Spaces: the case of the Municipal Development Forum of Igarapé-Açú, Pará, Amazonia

Abstract: This paper discusses how partnership between local organisations and Government inside governance spaces affects local development. The aim is to raise some critical issues about the concept of partnership and about partnership effectively for municipal development. Thus, the article uses partnership as its central theory. Specifically, it explores to what extent partnership is an effective strategy for local development in areas of historical conflict between local Government and local organisations in Pará S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The co-management aspect of a governance systems refers to the process that involves both private and public actors in formal interactions towards NRM. Governance in this context means a new arrangement of management in which in some way the social actors share values, ideas, power, and resources in favor of a common goal [68,69].…”
Section: Multi-partner Governancementioning
confidence: 99%
See 2 more Smart Citations
“…The co-management aspect of a governance systems refers to the process that involves both private and public actors in formal interactions towards NRM. Governance in this context means a new arrangement of management in which in some way the social actors share values, ideas, power, and resources in favor of a common goal [68,69].…”
Section: Multi-partner Governancementioning
confidence: 99%
“…There is uneven power among partners [69,100,113]. However, mutual cooperation in partnerships can be a mechanism for balancing unequal power relations [69,102]. Indeed, it was observed that there is mutuality in the cooperation between the core groups of partners in TNF.…”
Section: Multi-partner Governance System: Challenges and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation